Hubungan antara Emotional Abuse oleh Orang Tua dengan Self Esteem pada Remaja - Panggabean, Maria Elena; Hidayat, Briggita Sherly (Noetic Psychology, 2012)
AbstractEmotional abuse from parent was the most common type of abuse among children. It was also the most destructive effect to the children.Children who suffered from emotional abuse tend to have lower self esteem and lower self image. This research aimed to found the realtion between parental emotional abuse with teenager self esteem. Quantitative approach will be used in this research.ÃÂ Using purposive sampling method, 100 university student from West Jakarta were chosen as participant in this research. Data collected using emotional abuse scale and self esteem scale. The result of this research analyzed using pearson product moment with r = -.0401, p < .001. Based on this fionding, can be concluded that there was a striong and significant corelation between parental emotional abuse and teenager self esteem. ÃÂ Keywords : emotional abuse, self esteem, teenagerÃÂ